Indonesia Economic Prospects, July 2020 : The Long Road to Recovery - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) pandemic and associated containment measures triggered the deepest global recession in eight decades. As many countries implemented lockdowns and travel restrictions, global demand for goods and services plummeted along with tourism flows and commodity prices; supply chains were disrupted; and financial market volatility spiked. The Government of Indonesia also implemented mobility restrictions from mid-March and then a partial lockdown from April to June, preventing many firms and shops from operating, and discouraging many consumers from shopping. Hit by severe external and domestic shocks, economic activity tumbled. Real GDP growth slumped from 5.0 percent yoy in Q4 2019 to 3.0 percent in Q1 2020, the lowest quarterly growth since 2001. Private consumption slowed as mobility restrictions and personal avoidance behavior curbed household consumption. Investment growth also declined with heightened uncertainty and lower commodity prices. There was broad-based slowdown across sectors. Manufacturing, construction and low value-added service sectors including transport, storage, hotels and restaurants, sectors that employ a larger number of workers, all saw a near halving in their sectoral growth rates from Q4 2019. In contrast, growth of modern, knowledge-intensive services sectors, including digital, financial, education and health services accelerated. The slowdown in domestic demand and the unexpected growth in some manufactured exports helped narrow the current account deficit (CAD) to 2.5 percent of GDP in Q1 2020 from 2.7 percent of GDP in Q4 2019. The goods trade surplus soared, as some diversion of manufacturing production from China and higher palm oil prices earlier in the year propped up export values, while imports contracted due to lower consumption and, investment and falling oil prices. With the sudden stop in global travel and transport, both services exports and imports plunged.